Blockchain-enabled quality by design system for clinical trials - Vatankhah Barenji, Reza; Hariry, Reza Ebrahimi (Frontiers in Medicine, 2025)
IntroductionBlockchain technology offers a secure and distributed approach to data management that can strengthen the Quality by Design (QbD) framework in clinical trials. Integrating blockchain with QbD can enhance data integrity and promote participant safety.MethodsA blockchain-enabled QbD architecture was developed to support systematic quality improvement in clinical trials. The interactions among its components and peers were described, and a prototype was implemented using Hyperledger Fabric. Data from a pilot clinical trial were used to evaluate its applicability.ResultsThe prototype demonstrated that the proposed architecture efficiently facilitates immutable data exchange, enhances traceability among QbD activities, and supports secure collaboration between stakeholders. The system improved data consistency and enabled automated verification of trial processes.DiscussionThis study shows that blockchain technology can effectively enhance QbD implementation in clinical trials by improving data integration, transparency, and safety monitoring. The proposed architecture provides a feasible and scalable model for future clinical data management systems.